Canada : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2016)
This report evaluates the observance of standards and codes on Financial Action Task Force recommendations for anti-money laundering and combating the financing of terrorism (AML/CFT) in Canada. The findings reveal that the Canadian authorities have a good understanding of most of Canada's money laundering and terrorism financing risks. AML/CFT cooperation and coordination are generally good at the policy and operational levels. All high-risk areas are covered by AML/CFT measures, except legal counsel, legal firms, and Quebec notaries. This constitutes a significant loophole in Canada's AML/CFT framework. Law enforcement results are not commensurate with the money-laundering risk, and asset recovery is low.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Canada